Carbon fiber/thermoelectric Ag2S core–shell structure-based temperature–pressure dual-mode sensors - Junjie Zhu; Yuan Wang; Heng Liu; Size Lou; Min Shu; Miao Liu; Peng-An Zong; Chunlei Wan (Journal of Advanced Ceramics, 2025)
Dual-mode temperature–pressure sensors hold significant promise for personal health monitoring, wearable devices, and robotic signal detection. However, conventional designs that integrate two separate sensors complicate the fabrication process. This work presents a dual-mode temperature‒pressure sensor based on a core‒shell carbon fiber (CF)‒silver sulfide (Ag2S) film fabricated via facile electrodeposition (ED). The sensor employs its thermoelectric (TE) mechanism for self-powered temperature sensing, enabling accurate detection of finger touches and respiratory states, and exhibits the rapid response time of 0.7 s. For pressure sensing, its shell-to-shell contact ensures the ultrafast response time of 0.2 s, facilitating the precise monitoring of body movements. In addition to its sensing functionalities, the sensor demonstrated the superior electromagnetic interference (EMI) shielding efficiency of 50 dB (a twofold improvement), the tensile strength (TS) of 59 MPa (10× enhancement), and an antibacterial effectiveness of over 95%. These properties make it an excellent candidate for self-powered electronic sensor systems, paving the way for health monitoring, wearable technology, and artificial intelligence.